فن الخداع البصري ( أوب أرت ) وأهميته في فن الملصق الإعلاني (البوستر) (Latakia University Journal -Engineering Sciences Series, 2018)
Major development took a place in contemporary art movement since 19th century and has been affected by historical events; optic art has started after appearing of pop art and other abstract and Dadaism movements in many kinds of visual and movements arts. this progress Accompanying with Mutual influence between arts and sciences represented of some panting a, sculpture and photograph artists, Vasarely and Calder and others ,op art started  in tow dimensions then with three dimensions,between defrences scientific ,mathematics, philosophic ,media and thinking aspects Accompanying with booster art which been affected by different kinds of visual with panting and photography art and sometimes with in  relief  including thinking, philosophic and Technique shorthand. poster art consider vital and modern art  in it's different aspects like economical ,educational, scientific, political, cultural and Literary and Arabic and European arts have benefit from it since between the two war until now. فن الخداع البصري ( أوب  أرت ) وأهميته في فن الملصق الإعلاني (البوستر) لقد حصل تطور كبير في تيارات الفن المعاصر منذ القرن التاسع عشر وتأثرت بالأحداث التاريخية ، وقد ظهر فن الخداع البصري (أوب أرت) إثر ظهور الفن الشعبي (بوب أرت) و مختلف الاتجاهات التجريدية والدادائية في العديد من  أنواع  الفنون البصرية الحركية . ترافق هذا التطور بالتأثير المتبادل بين الفنون و العلوم متمثلةً بأعمال بعض فناني التصوير والنحت والفوتوغراف ، وقد برزت بقوة أعمال فازارللي وكالدر  وغيرهم ، وكان فن خداع البصر ببعدين ثم بثلاثة أبعاد ، وضمن مختلف المؤثرات العلمية والرياضية والإعلامية و الفكرية والفلسفية ظهر بالتوازي معها فن الملصق(البوستر) الذي استعان بشتى أنواع الصورة بالرسم والفوتوغراف وأحياناً بالبروزات (الرولييف ) متضمناً الاختزال الفكري والفلسفي والتقني . يعتبر فن الملصق بأنواعه المختلفة، الثقافية والأدبية والسياسية والاقتصادية والتعليمية والعلمية فناً معاصراً حيوياً استفاد منه الفنانون الآوربيون والعرب منذ مابين الحربين حتى اليوم.